An Examination of block V at the site of Pirque Alto in Cochabamba, Bolivia : a household archaeological perspective - Sitek, Matthew J. (My University, 2010)
One of the most recent trends in archaeological research has become known as household archaeology; its primary focus being the excavation and analysis of domestic remains. This relatively recent shift in direction for many archaeologists is providing a fresh view of not only how individual household populations lived, but also how these small units of people were influenced, affected, and changed, over time, by broader cultural factors of prehistory. For this reason household archaeological approaches will be employed to investigate the household structure and associated remains uncovered at the site of Pirque Alto (CP-11); a site outside of Cochabamba, Bolivia in the South Central Andes Mountains. A variety of statistical tests will be utilized to indicate everyday activity areas (processing food, food consumption, refuse disposal, etc.) that took place in and around the household. This study will help future researchers understand the overall prehistoric context of the site of Pirque Alto and give a general view of what life was like for Cochabamba populations during the Middle Horizon (A.D. 500 - 1000); a time characterized by the strong influence of the state level society, Tiwanaku.
Keywords: Pirque Alto Site (Bolivia); Households -- Bolivia -- Cochabamba.; Tiwanaku culture -- Bolivia -- Cochabamba.; Indians of South America -- Bolivia -- Cochabamba -- Antiquities.; Excavations (Archaeology) -- Bolivia -- Cochabamba